Smart manufacturing innovation and transformation : interconnection and intelligence - Luo, Zongwei, 1971- (Business Science Reference, 2014)
"This book covers both theoretical perspectives and practical approaches to smart manufacturing research and development triggered by ubiquitous interconnection and intelligence, discussing the transformation of manufacturing, the latest developments in smart manufacturing innovation, current and emerging technology opportunities, and market imperatives that enable manufacturing innovation and transformation"-- Provided by publisher.
"Premier reference source"--Cover.
Keywords: Manufacturing processes -- Automation.; Flexible manufacturing systems.; Production engineering.; Manufacturing industries -- Technological innovations.; elektronické knihy; electronic books